A cone-beam computed tomography-guided endodontic management of internal variations in the root canal anatomy of maxillary molar - Ankush Kumar; Mischeal Kaur Sawhney; Munish Goel; Shweta Verma (Wolters Kluwer Medknow Publications, 2024)
This case report aims to present and analyze the internal variations in root canal anatomy of a maxillary molar and its successful non-surgical endodontic management using CBCT guidance. This clinical report aims to emphasize the importance of recognizing atypical dental internal anatomy during endodontic treatment and to describe a case where the presence of two palatal roots in the maxillary molar was identified and was managed successfully. This report presents a case where endodontic treatment was performed on a maxillary molar with unusual pulpal and periapical findings. During the treatment, the presence of two palatal roots in the tooth was observed, and relevant treatment modalities were discussed for the treatment's success. Understanding the internal anatomy of teeth is crucial in clinical and radiographic examinations. This knowledge is essential for detecting unusual roots and canals and ensuring effective cleaning and shaping of calcified canals, which are often overlooked in endodontic treatment.